Kyrgyz Republic : Moderating Growth and a Challenging Outlook - World Bank Group (Washington, DC, 2014)
Political developments at home and abroad have been prominent this year. Domestically, a new government was formed quickly after one of the coalition parties withdrew the support to Prime Minister Satylbaldiev in March, 2014. The new government, led by Prime Minister Djoomart Otorbayev, represents the same coalition of political parties providing continuity on most policies but also a fresh momentum for reforms in key sectors. The next round of parliamentary elections is scheduled for the autumn 2015. Internationally, the Kyrgyz Republic has made firm commitments towards accession to the Customs Union of Belarus, Kazakhstan and Russia while tensions have appeared in relations with some neighbors. Growth has slowed down significantly and we have revised our projection for real GDP growth to 3 percent for 2014 as a whole from the 4 percent we projected in April. Despite robust government investment and gold exports, economic activity has moderated as the slowdown in Russia, the winding down of operations at the Manas Transit Center and increased tensions in trade relations with neighbors are affecting remittances and non-gold exports. Economic activity has been further affected by the poor agriculture harvest while difficulties expected in ensuring stable energy supply in the winter may add a further drag on activity in the rest of the year. Fast growth rates in credit to the private sector and in construction are leveling off as businesses report a more difficult operating environment.